Counting Shadows – Measuring trafficking in Persons in Australia - Wise, Matthew; Schloenhardt, Andreas (International Journal of Criminology and Sociology, 2014)
The true extent and nature of trafficking in persons in Australia remains a mystery despite wild speculations about the scale of this problem. This article aims to dispel some of the confusion surrounding trafficking in persons by examining the claims made about the prevalence of this offence and displacing many of the myths about the number of victims in Australia. This involves an analysis of the Australian Government’s approach to data collection and a critical examination of the data provided by non-official sources, especially non-governmental organisations and advocacy groups. The article also investigates the ‘dark figure’ of trafficking in persons in Australia and concludes by developing recommendations to measure trafficking in persons in Australia more accurately and by offering directions for further research in this field.